Nghiên cứu thành phần hóa học và hoạt tính của nấm nội sinh phân lập từ cây nghệ vàng - Hiếu, Nguyễn Ngọc; Đức, Nghiêm Văn; Dung, Phạm Thị; Tú, Dương Ngọc (Vietnam Journal of Chemistry, 2016)
In the present study, 14 substances were isolated from Fusarium oxysporum, one endophytic fungi isolated from Curcuma longa. Their structures were elucidated by GC/MS and NMR experiments. In addition, the bioactivity screening test with crude extracts of Fusarium oxysporum cultivation at 1500 ppm showed a high antimicrobial effectivity on Botrytis cinerea with 56.46 %. Keywords. Fusarium oxysporum, Botrytis cinerea, Curcuma longa, Endophytic fungi.